ANALISIS OPERASIONAL DALAM PENGENDALIAN INTERNAL ATAS KETERSEDIAAN BARANG DAGANG PT. KIMIA FARMA BATAM - Alifia Lisda Zetty Aqmi; Fendy Cuandra; Muhammad Saprudin; Muhammad Syachrani Hafidz; Stefania Rumapea (Jurnal Bina Manajemen, 2023)
This study aims to analyze the operations at PT. Kimia Farma before, during and after the covid-19 pandemic. The Covid-19 pandemic has an impact on all sectors including the health sector, so further analysis is carried out regarding the operational changes that have occurred at PT. Kimia Farma. The research method used is a qualitative approach by processing secondary data. The results of this study summarize the operations of PT. Kimia Farma in designing a product both finished products and raw materials, warehouse locations, factories, research sites and company assets such as strategic medicine gardens, supply chain processes to inventory management PT. Kimia Farma.